Optics Communications Implementation Perspective on IEEE 802.15.7-2018 Optical Camera Communication Modes - Van Khoa Pham; N. L. Nguyen; Trang Nguyen; Thong Nguyen Duy (My University, 2025)
Optics Communications Implementation Perspective on IEEE 802.15.7-2018 Optical Camera Communication Modes
Keywords: OCC; IEEE 802.15.7; Optical Camera Communication